The Erythrocyte Catalase Enzyme Activity in Iranian Osteoporotic Women: Catalase and bone mineral density - Behrooz Jannat; Mohammad-Reza Oveisi; Naficeh Sadeghi; Mannan Hajimahmoodi; Golnaz Izadi Dolagh; Masoomeh Behzad; Ahmad-Reza Jamshidi; Abdol-azim Behfar; Kheir-ollah Gholami (Iranian Journal of Pharmaceutical Sciences, 2010)
Osteoporosis is a disease of high prevalence with increased bone loss. It has potential public health threat and that the health authorities had taken several measures for its control. In recent years, considerable attention has been given to physiopathology of osteoporosis. Oxidative stress has been proved to be involved in bone resorption. Oxidative stress occurs when balance between oxidants and biochemical antioxidants is disrupted because of excess reactive oxygen species. Thus, we measured catalase activity, as one of the marker of stress oxidative, in 138 women. Participants were selected by inclusion and exclusion criteria from those who were referred to Jamie Clinic in Tehran for BMD evaluation. Catalase antioxidant activity was 262.01±44.70 k/gHb in the group of subjects with osteoporosis in comparison with the group of healthy subjects, 273.77±46.92 k/gHb. The results show that catalase activity in patients with bone deficiency was less than in the control group, though it was not significant. This difference was more between control and patients group with more acute disease (T score -1.7) than patients group with milder disease (T score<-1).The results show that it may be useful to monitor osteoporosis in the more expanded sample size to obtain more definition results.